McDonald's global expansion : adaptation and differences in taste - Baack, Daniel W.; Harris, Eric G.; Baack, Donald ([London] : SAGE, 2016)
There is no doubt that McDonald's has been successful in developing and maintaining a recognizable global brand. This case study examines the McDonald's global brand strategy and evaluates the adaptations that the company makes for local, national markets.
Originally Published in: Baack, D. W., Harris, E. G., & Baack, D. (2012). McDonald's Global Expansion: Adaptation and Differences in Taste. In International marketing (pp. 263-264). Los Angeles: SAGE Publications, Inc. ISBN: 9781452226354.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; McDonald's Corporation; Export marketing -- Case studies; Consumers' preferences -- Case studies; Brand name products -- Case studies